The Effect of Using Audio-Visual in Implementation Curriculum Merdeka on Speaking Skill on Eighth Grade at SMP N 5 Limbur Lubuk Mengkuang - Lufiah, Zumrotun; Saputra, Riyadi; Saputri, Erva Nuri (Innovative: Journal Of Social Science Research, 2024)
Effective communication in a foreign language is essential for a student's development. However, many students find it difficult to speak due to limited vocabulary, fear of mispronunciation, or lack of interest in English classes. To overcome these challenges, researchers used audiovisual media as a teaching tool to improve students' speaking skills. This study was conducted in the second semester of Class VIII of SMPN 5 Limbur Lubuk Mengkuang in 2024 using the pre-experimental method and group pre-test-post-test design. The results of the analysis showed a significant increase, with the average pre-test score increasing from 43.20 to 75.40 post-test after using audiovisual aids. Hypothesis testing using the Wilcoxon test obtained a two-sided significance value of 0.00 which indicated a significant difference between the results of the treatment before and after audiovisual. It can be concluded that the integration of audiovisual media improves the speaking skills of class VIII students of SMPN 5 Limbur Lubuk Mengkuang positively and significantly.